DESAIN E-VOTING PILKADA KOTA BOGOR MENGGUNAKAN PROTOKOL TWO CENTRAL FACILITIES YANG DIMODIFIKASI - Kusumah, Fitrah Satrya Fajar; Guritman, Sugi; Giri, Endang Purnama (Krea-TIF: Jurnal Teknik Informatika, 2015)
One of Indonesian election is the local elections for regional head that are still using conventional election type. The conventional election type still spend a lot of time and prone of mistakes made by humans, including frauds committed by certain parties. This research is based on two central facilities protocol in Schneier book (1996) and a continuation of previous research by Sireesha and Chakchai (2005) which has developed a secure election with two central facilities protocol that implement the development of Central Legitimization Agency (CLA) and the Central Tabulating Facilities (CTF) to create a secure virtual elections and Wardhani (2009) which implement the protocol Two central facilities at IPB online voting. This research collaboration with the KPU Bogor and Bogor Information and Communications, for the purposes of analyzing and studying the various elections policy of regional heads of Bogor. Through this study found a design system using a protocol e-voting Two central facilities modified. However, this design is still require further research to be applicable for Bogor Regional Head election.